THE STUDY OF MUTUAL LEGAL ASSISTANCE MODEL AND ASSET RECOVERY IN CORRUPTION AFFAIR - Muhammad Rustamaji; Bambang Santoso (Universitas Negeri Semarang, 2019)
The release of Indonesia Corruption Watch stated that the value of state losses due to corruption cases increased significantly from 2016 to 2017. Through Sociolegal research, this study utilizes a purposive random sampling technique. Data collection techniques used in-depth interviews, observation, documentation and Focus Group Discussion. The data analysis technique uses Miles and Huberman’s interactive analysis. Based on the new mechanism, this study succeeded in revealing the positive aspects of the regulation of seizure of assets resulting from corruption in foreign countries based on the Mutual Legal Assistance Agreement. The research produced findings on the functioning of law enforcement agencies and related institutions in Indonesia in an effort to seize assets resulting from corruption and money laundering stored abroad. In more detail, based on the conception of the reality of cooperation, it is known that in the context of eradicating criminal acts of corruption, failure to return assets resulting from corruption can be said to reduce the 'meaning of punishment' against corruptors. The development of such thinking implies that the eradication of corruption lies not only in the prevention and punishment of corruptors, but also includes actions that can restore asset recovery due to extraordinary crimes. Deprivation of assets resulting from corruption is primarily carried out abroad through Mutual Legal Assistance is a mechanism of international cooperation relating to investigations, prosecutions, and hearings in court proceedings in accordance with the provisions of the state legislation requested.